Ex-post Merger Evaluation in the UK Retail Market for Books - Luca Aguzzoni; Elena Argentesi; Lorenzo Ciari; Tomaso Duso; Massimo Tognoni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This paper empirically evaluates the price effects of the merger of two major book retail chains in the UK: Waterstone's and Ottakar's. We employ differences-in-differences techniques and use a rich dataset containing monthly scanner data information on a sample of 200 books sold in 60 stores in 50 different local markets for a period of four years around the merger. Since retail mergers may have either local or national effects (or both) according to the level at which retail chains set prices, we undertake an ex-post assessment of the impact of the merger at both levels. At the local level, we compare the changes in the average price charged before and after the merger in the shops located in overlap areas –i.e. areas where both chains were present before the merger– and in non-overlap areas –i.e. areas where only one chain was present before the merger. At the national level, we employ two distinct control groups to evaluate the merger, namely the competitors and the top-selling titles. We find that the merger did not result in an increase in prices either at the local or at the national level. We also perform heterogeneous treatment effects estimations in order to assess whether the effect of the merger differs along various dimensions of heterogeneity that are present in our data.
Keywords: K21; L24; L44; D22; O32; 330